RNA driving the epigenetic bus - Mattick, John S (Nature Publishing Group, 2012)
EMBO J 31 3, 522–533 (2012); published online 12232011 For many years, it has been assumed that mammalian development is primarily controlled by transcription factors, but recent studies, including that reported by Ng et al (2012) in this issue, indicate that there is an additional massive hidden layer of regulatory RNAs that control the site specificity of chromatin-modifying complexes and other regulatory proteins involved in the control of embryological and neural differentiation.